ANALISIS PENGARUH FOREIGN DIRECT INVESTMENT, PENANAMAN MODAL DALAM NEGERI, DAN GROSS DOMESTIC PRODUCT TERHADAP EMISI KARBON DI INDONESIA - Rizki, Christine Amalia; Anggraeni, Puspitasari Wahyu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The purpose of this paper is to analyze the effect of Foreign Direct Investment inflows, Domestic Direct Investment, and Gross Domestic Product on carbon emissions in Indonesia both in the long and short run from 1990 to 2020. Error Correction Model (ECM) is used to answer the empirical questions regarding long-term and short-term relationships between research variables. The results of this study indicate that FDI has a negative and significant relationship on carbon emissions in the long term in Indonesia, but doesn’t have a significant relationship in the short term. PMDN has a positive and significant relationship on carbon emissions in the long term in Indonesia, but doesn’t have a significant relationship in the short term. Gross Domestic Product has a positive and significant relationship on carbon emissions in the long and short term in Indonesia.